The potential of phenolic acids in therapy against snakebites: A review. (March 2022) - Ferreira, Sarah de Sousa; Silva, Diana Pontes da; Torres-Rêgo, Manoela; Silva-Júnior, Arnóbio Antônio da; Fernandes-Pedrosa, Matheus de Freitas
Abstract: Ophidism is a serious health problem worldwide and is included in the World Health Organization's (WHO's) list of Neglected Tropical Diseases. Although snakebite envenoming requires emergency treatment, currently the only treatment recommended by WHO is serotherapy, which has some disadvantages such as low access to the rural population, low effectiveness in neutralizing local effects, and high cost. In this context, new alternatives for the treatment of snakebites are required. The use of plant-derived compounds to inhibit the effects caused by snake venoms has been the object of a number of studies in recent years. This review aims to provide an up-to-date overview of the use of phenolic acids with therapeutic application against envenomation by snakes of different species. In this sense, structural analysis in silico and biological activities in vivo and in vitro were reported. The acids were subdivided into derivatives of benzoic and cinnamic acids, with derivatives of cinnamic acids being the most studied. Studies have revealed that these compounds are capable of inhibiting local and systemic effects induced by envenomation, and structural analyses indicate that the acids interact with important sites responsible for the action of toxins. Thus, it was reported that phenolic acids showed antiophidic potential, providing insights for future research to develop complementary drugs for the treatment of snakebites. Graphical abstract: Image 1 Highlights: Snakebite causes high numbers of mortality and morbidity in the world. Phenolic acids inhibit symptoms of envenomation by snake venoms. Toxins were inhibited after treatment with phenolic acids. The acids inhibit the action of toxins from different snake genera. Phenolic acids can be complementary alternatives to serum therapy.